The Hermeneutics of Muhammad Arkoun: Reconstructing Islamic Epistemology through a Critique of Islamic Reason - Muhammad Kurniansyah; Barsihannor, B; Muhaemin Latif (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the thought of Mohammad Arkoun as one of the prominent figures in contemporary Islamic intellectual reform. The discussion focuses on three main aspects: Arkoun’s intellectual biography, his hermeneutical approach, and his project of critiquing Islamic reason as an effort toward epistemological reconstruction in Islam. Using a qualitative approach based on library research, this study analyzes Arkoun’s major works as well as relevant academic literature. The findings indicate that Arkoun’s intellectual background, shaped at the intersection of Islamic tradition and modern Western thought, led him to develop a critical hermeneutics that views the Qur’an and Islamic tradition as historical discourses open to reinterpretation. Arkoun’s critique of Islamic reason aims to expose the epistemological limitations of traditional Islamic thought, which tends to be normative and ideological. In the contemporary context, Arkoun’s ideas remain highly relevant as an attempt to reconstruct Islamic epistemology, foster a constructive dialogue between Islam and modernity, and offer a critical perspective on the ideologization of religion in political and social life. Thus, Arkoun’s thought contributes significantly to the development of Islamic studies that are more humanistic, reflective, and responsive to the challenges of the modern world.